2019
DOI: 10.30919/esmm5f237
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Transport within Periodic Porous Structures — From Classical Phonon Size Effects to Wave Effects

Abstract: ΩSolid angle SubscriptsGPnC SiNW Graphene phononic crystal Silicon nanowire NCJ_MC Nano-cross-junction system with its thermal conductivity calculated by the Monte Carlo method NCJ_AGFMC Nano-cross-junction system with its thermal conductivity calculated by the AGFMC method AbstractTailoring thermal properties with nanostructured materials can be of vital importance for many applications. Generally classical phonon size effects are employed to reduce the thermal conductivity, where strong phonon scattering by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 135 publications
(253 reference statements)
0
20
0
Order By: Relevance
“…In this work, a simple but accurate analytical model is developed, which extends our previous work on nanoporous films 14,20 to dry-etched nanowires and general thin-film-based nanoporous structures. The model predictions agree well with frequency-dependent phonon Monte Carlo (MC) simulations that incorporate the specularity of individual surfaces and the exact three-dimensional structures.…”
Section: Introductionmentioning
confidence: 82%
“…In this work, a simple but accurate analytical model is developed, which extends our previous work on nanoporous films 14,20 to dry-etched nanowires and general thin-film-based nanoporous structures. The model predictions agree well with frequency-dependent phonon Monte Carlo (MC) simulations that incorporate the specularity of individual surfaces and the exact three-dimensional structures.…”
Section: Introductionmentioning
confidence: 82%
“…With tunable phonon transport and electron band structures, these 2D porous structures are named as antidot lattices, nanomeshes, or phononic structures. [16], [151] Several 2D porous structures have been theoretically investigated for thermal, electronic, and thermoelectric properties, including the most studied graphene antidot lattices (GAL), [151 porous silicene, [162] and 2D MoS2 and phosphorene antidot lattices. [163[164] On the one hand, phonon transport in these porous structures can be significantly suppressed by boundary scattering and localization of phonons around the pores, as well as wave-like phonon interference in periodic structures.…”
Section: Nanoribbonsmentioning
confidence: 99%
“…[163[164] On the one hand, phonon transport in these porous structures can be significantly suppressed by boundary scattering and localization of phonons around the pores, as well as wave-like phonon interference in periodic structures. [16], [155], [156] On the other hand, the electronic band structure can be tailored in well-designed porous structures so that the Seebeck coefficient can be enhanced while the electrical conductivity can remain high. [157 [164] Up to now, several theoretical studies have demonstrated enhanced ZT values in 2D porous structures, as listed in Table 2.…”
Section: Nanoribbonsmentioning
confidence: 99%
See 2 more Smart Citations